Analisis Perubahan Kepemimpinan terhadap Integritas, Kedisiplinan, dan Kinerja Karyawan di Kantor Badan Perencanaan Pembangunan Daerah Kabupaten Simeulue - Mesa, Aidil Aria; Husen, Tamitha Intassar (Regress: Journal of Economics & Management, 2025)
Organizational change, particularly leadership transition, often reshapes institutional culture, regulatory practices, and employee behavior. This study examines whether changes in leadership significantly affect employee integrity, discipline, and performance at the Regional Development Planning Agency of Simeulue Regency. Using a qualitative approach supported by observation and in-depth interviews, the research analyzes behavioral and structural adjustments occurring during the leadership transition phase. The findings indicate that leadership change influences organizational culture and regulatory patterns, particularly during the adjustment period, as each leader brings distinct characteristics, perspectives, and managerial approaches. These differences affect employee discipline through variations in supervision and control mechanisms; however, they do not significantly alter overall employee performance, which is more strongly determined by individual competence and personal attributes. The study concludes that leadership change primarily generates short-term adaptive shifts rather than substantial long-term transformations in integrity, discipline, or performance.